2014
DOI: 10.1186/s12862-014-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic evolution of the alpha (α) and beta (β) keratins has accompanied integument diversification and the adaptation of birds into novel lifestyles

Abstract: BackgroundVertebrate skin appendages are constructed of keratins produced by multigene families. Alpha (α) keratins are found in all vertebrates, while beta (β) keratins are found exclusively in reptiles and birds. We have studied the molecular evolution of these gene families in the genomes of 48 phylogenetically diverse birds and their expression in the scales and feathers of the chicken.ResultsWe found that the total number of α-keratins is lower in birds than mammals and non-avian reptiles, yet two α-kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 78 publications
(127 reference statements)
3
113
0
4
Order By: Relevance
“…Furthermore, comparative genomic studies showed that the number of α-and β-keratin genes and β-keratin gene diversity were important for feather evolution and the adaptation of birds to diverse ecological niches (13,14,24,25). Apparently, compositional changes of keratins are associated with different avian lifestyles.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, comparative genomic studies showed that the number of α-and β-keratin genes and β-keratin gene diversity were important for feather evolution and the adaptation of birds to diverse ecological niches (13,14,24,25). Apparently, compositional changes of keratins are associated with different avian lifestyles.…”
Section: Significancementioning
confidence: 99%
“…A recent study found that regulatory innovations of feather development genes predate the origin of feathers, suggesting that the avian dinosaur ancestor already had the nonkeratin protein-coding toolkit for making feathers (12). While fewer new genes have been found in bird genomes (13) and the α-keratin gene family has shrunk in birds relative to mammals and reptiles (14,15), the expansion of β-keratin genes is one of the most unique genomic features of birds (13,14).…”
mentioning
confidence: 99%
“…Beta-keratins (or 'corneous beta-proteins' [7][8][9][10]) are insoluble, rigid, fibrous, structural proteins distinct from alpha-keratins in composition and structure. They are expressed only in reptiles and birds (sauropsids) [11][12][13], suggesting that this gene family originated after the divergence of sauropsids from other vertebrates [5,[14][15][16]. The beta-keratins have in common a core of approximately 30 amino acids and produce filaments (microfibrils) 3 nm in diameter [17].…”
Section: Introductionmentioning
confidence: 99%
“…A study of keratin genes, which are important for the evolution of feathers early or just before the avian radiation, is an example of how to use whole genome information to gain knowledge about flight evolution in birds in general (Greenwold et al 2014). Comparative gene family evolution across birds, and also mammals, has been shown to become highly informative by two exemplary studies: the adaptive gene complex of avian haemoglobin isoform expression (Opazo et al 2014) and a general vertebratewide analysis of hedgehog genes, which are key switches during embryonal development (Pereira et al 2014).…”
Section: A First Phylogenomic Avian Tree Of Lifementioning
confidence: 99%